Suppressors of gene 32 am mutants that specifically overproduce P32 (unwinding protein) in bacteriophage T4. - Wood, W J (1977)
A gene 32 amber (am) mutant, amNG364, fails to grow on Escherichia coli Su3+ high temperatures, suggesting that the tyrosine residue inserted at the am codon by Su3+ leads to a temperature-sensitive gene 32 protein (P32). By plating amNG364 on E. coli Su3+ 45 degrees C, several pseudorevertants were found that proved to contain a suppressor (su) mutant in addition to the original am mutation. Crosses of two of these amNG364su strains to am+ phage indicated that the suppressors themselves are in or close to gene 32. Phage strains carrying either of the two su mutations, without amNG364, grew normally. When cells were infected by these su mutants and the proteins produced were examined by sodium dodecyl sulfate-gel electrophroesis, specific overproduction of P32 was found. Maximum overproduction compared to am+ phage was 6.6-fold for one su mutant and 2.4-fold for the other. Other proteins were produced in normal amounts and in normal time sequence. When amNG364su phage were allowed to infect E. coli S/6/5(Su-), the gene 32 am fragments produced were present at the same derepressed levels as in an infection by amNG364 without a suppressor. The suppressor mutations are interpreted as causing derepression of P32 by altering sites in this autogenously regulated protein involved in template recognition. Previously, specific derepression of gene 32 had only been shown using gene 32 conditional lethal mutants grown under restrictive conditions. We have shown that P32 can also be derepressed under permissive conditions, indicating that loss of P32 function is not necessary for specific derepression.